The effects of Tai Chi exercise on sleep quality among the elderly: a study based on polysomnographic monitoring - Wang, Chao; Jiang, Tao; Li, Hansen; Cao, Guikang; Zhang, Guodong (Frontiers in Neurology, 2024)
Sleep problems contribute to an increased risk of depression, cardiovascular issues, and various other diseases among older individuals. Consequently, enhancing the quality of sleep in this demographic has become a pressing concern. The objective of this study was to investigate the impact of an eight-week Tai Chi exercise intervention on the sleep quality of older adults.